CENTRAL AMERICA AND THE UNITED STATES CYCLES OF CONTAINMENT AND RESPONSE - Booth, John A. (2015)
In the 80s as a result of the conflicts thatlived Central America, the region was facingthe task of finding the right path to peace.This became one of the most important itemson the agenda of the United States, which wasable to make during the lull of Vietnam.